What to Do? Thoughts Evoked by the Census of Moscow - Tolstoy, Leo, graf, 1828-1910; Hapgood, Isabel Florence, 1850-1928 (Salt Lake City, UT : Project Gutenberg, 2003)
"What to Do? Thoughts Evoked by the Census of Moscow" by graf Leo Tolstoy is a reflective essay written during the late 19th century. In this treatise, Tolstoy explores the social implications and moral responsibilities associated with conducting a census in Moscow, encouraging a deep examination of societal conditions and the human experience related to poverty and suffering. At the start of the essay, Tolstoy recounts his shock at witnessing the stark poverty in Moscow after moving from the countryside. Through encounters with beggars and the systemic issues of urban life, he contemplates the disconnection between the wealthy and the suffering classes. He highlights individuals who live in dire conditions, raising questions about societal indifference and moral obligation. As Tolstoy reflects on the gathering of census data, he emphasizes that the process should not merely catalog the suffering but should also embody a call to action, urging those involved to engage with the lives behind the statistics and foster human connection rather than mere observation. His argument sets the stage for a broader discourse on empathy, social justice, and the responsibility of individuals towards those in need. (This is an automatically generated summary.)
On Women -- On Labor And Luxury
Release date is 2003-01-01
Transcribed from the 1887 Tomas Y. Crowell edition by David Price
Keywords: Social problems; Moscow (Russia) -- Social conditions